2022
DOI: 10.1002/pds.5557
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to nitrosatable drugs during pregnancy and childhood cancer: A matched case–control study in Denmark, 1996–2016

Abstract: Background Nitrosatable drugs can be synthesized to N‐nitroso compounds in human stomach. In a pregnant woman, N‐nitroso compounds can be translocated to the fetus through the placenta. Maternal exposure of nitrosatable compounds during pregnancy has been associated with childhood brain tumors and leukemia. However, few studies have investigated an association between nitrosatable drug exposure during pregnancy and childhood cancer. We examined if maternal prescriptions of nitrosatable drugs received during pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 79 publications
0
5
0
Order By: Relevance
“…44 Furthermore, doxycycline is considered a nitrosatable drug, and maternal prescriptions of nitrosatable drugs have also been associated with childhood ALL. 15 While our findings should be considered exploratory, they suggest associations between the prescription of beta-lactam antibacterials (excluding penicillin) during pregnancy and the occurrence of childhood hepatoblastoma. In contrast, a cohort study conducted in Denmark and Sweden found no associations between maternal prescriptions of other beta-lactam antibacterials and the risk of childhood cancers (HR = 0.88; 95% CI: 0.50-1.57).…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…44 Furthermore, doxycycline is considered a nitrosatable drug, and maternal prescriptions of nitrosatable drugs have also been associated with childhood ALL. 15 While our findings should be considered exploratory, they suggest associations between the prescription of beta-lactam antibacterials (excluding penicillin) during pregnancy and the occurrence of childhood hepatoblastoma. In contrast, a cohort study conducted in Denmark and Sweden found no associations between maternal prescriptions of other beta-lactam antibacterials and the risk of childhood cancers (HR = 0.88; 95% CI: 0.50-1.57).…”
Section: Discussionmentioning
confidence: 86%
“…Notably, doxycycline, a commonly used drug from the tetracycline group, has been found to increase the average number of megakaryocytes and the periportal leukocytic infiltration in liver cells, as well as causing DNA damage, in a study on rat embryonic development 44 . Furthermore, doxycycline is considered a nitrosatable drug, and maternal prescriptions of nitrosatable drugs have also been associated with childhood ALL 15 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…with poor oral health), more alkaline stomach pH (facilitating bacterial proliferation) and with a high intake of other sources of amines (red meat or certain drugs) and low intake of NOC inhibitors (polyphenols, vitamin C). Pregnant women can experience physiological changes that may make them more prone to endogenous formation of NOC [65,66]. While it would be unethical to randomise pregnant women to conditions that could put them or their baby at risk, future studies could investigate these biological mechanisms in non-randomised observational studies of pregnant women or randomised control trials of non-pregnant volunteers.…”
Section: Plos Watermentioning
confidence: 99%